Catch 22: wetlands protection and fishing for survival. (28th October 2015) - Gillespie, Josephine
Abstract: Environmental regulation of biodiversity hotspots, including wetlands, is of increasing importance in an era when species and habitat loss is common. A number of global environmental protection regimes attempt to set up processes that protect vulnerable species and their habitats. One such regulatory regime, the Ramsar Convention (Convention on Wetlands of International Importance, especially as Waterfowl Habitat), provides overarching protection for hundreds of wetlands around the world. In this paper, one Ramsar listed wetland, Southeast Asia's and Cambodia's largest freshwater lake, the Tonle Sap, is subject to a legal geographical analysis. A legal geography approach – one that puts front and centre an examination of both the environmental protection regulations for the wetlands and the people subject to them – enables the complexity of the legal‐human–environment dynamic in this unique wetlands to be revealed. Measuring the success, or otherwise, of environmental protection regulations requires an understanding of both the biophysical and social dynamics of the place subject to that protection. Geographers, particularly legal geographers, are well placed to document the human–environment dimensions of place and to expose fragilities or disconnections between regulations and place. Regulations that do not take adequate account of complex people–place dynamics are likely to fall short of expectations and run the risk of becoming self‐defeating, giving rise to a potential catch‐22 scenario.